Delayed Effects of Acute Reperfusion on Vascular Remodeling and Late-Phase Functional Recovery After Stroke - Durán-Laforet, Violeta; Fernández-López, David; García-Culebras, Alicia; González-Hijón, Juan; Moraga, Ana; Palma-Tortosa, Sara; García-Yébenes, Isaac; Vega-Pérez, Adrián; Lizasoain, Ignacio; Moro, María Ángeles (Frontiers in Neuroscience, 2019)
Tissue perfusion is a necessary condition for vessel survival that can be compromised under ischemic conditions. Following stroke, delayed effects of early brain reperfusion on the vascular substrate necessary for remodelling, perfusion and maintenance of proper peri-lesional hemodynamics are unknown. Such aspects of ischemic injury progression may be critical for neurological recovery in stroke patients. This study aims to describe the impact of early, non-thrombolytic reperfusion on the vascular brain component and its potential contribution to tissue remodelling and long-term functional recovery beyond the acute phase after stroke in 3-month-old male C57bl/6 mice. Permanent (pMCAO) and transient (60 min, tMCAO) brain ischemia mouse models were used for characterizing the effect of early, non-thrombolytic reperfusion on the brain vasculature. Analysis of different vascular parameters (vessel density, proliferation, degeneration and perfusion) revealed that, while early middle cerebral artery recanalisation was not sufficient to prevent sub-acute vascular degeneration within the ischemic brain regions, brain reperfusion promoted a secondary wave of vascular remodelling in the peri-lesional regions, which led to improved perfusion of the ischemic boundaries and late-phase neurological recovery. This study concluded that acute, non-thrombolytic artery recanalisation following stroke favours late-phase vascular remodelling and improves peri-lesional perfusion, contributing to secondary functional recovery.